A new Caryophyllaceae-feeding species of Macrosiphum (Hemiptera: Aphididae) in Republic of Georgia, and a redescription of Macrosiphum hartigi Hille Ris Lambers - Barjadze, Shalva; Barbagallo, Sebastiano; Blackman, Roger; Özdemir, Işil (Zootaxa, 2017)
Apterous and alate viviparous females and the alate males of Macrosiphum eastopi Barjadze & Blackman sp. n. living on Oberna multifida Ikonn. (=Silene multifida Rohrb.) (Caryophyllaceae) are described from the Republic of Georgia (Caucasus). Type specimens are deposited at the Institute of Zoology, Ilia State University (IZISU), Tbilisi, Georgia; the Natural History Museum (BMNH), London, U.K.; and the University of Catania (UCI), Sicily, Italy. Apterous and alate viviparous females of its close relative M. hartigi Hille Ris Lambers, 1947, living on Silene vulgaris (Moench) Garcke and Stellaria holostea L. (Caryophyllaceae) are redescribed, based on co-types and other material from Austria, France, Italy and Switzerland. The hitherto unknown fundatrix, oviparous females and alate males of M. hartigi are described from Italy and Switzerland. Macrosiphum eastopi sp. n. is differentiated from the morphologically similar M. hartigi and compared with other Macrosiphum species living on Caryophyllaceae. A key is provided to apterous viviparous females of all aphid species recorded on Oberna multifida.